FORMULATION OF RED BETEL LEAF EXTRACT LOTION (Piper crocatum Ruiz & Pav) AS SUNSCREEN - Rantika, Nopi; Hindun, Siti; Najihudin, Aji; Auliasari, Nurul; Khoerunisa, Winna; Sopiah, Siti (Faculty of Mathematic and Natural Science, Garut University, 2024)
Betel leaf is a natural ingredient that people use as a traditional medicine. One of the ingredients found in red betel leaves is a phenolic compound in the form of flavonoids, a photoprotective substance that can be used as protection from UV radiation. Sunscreen is a cosmetic preparation that can protect the skin from UV radiation and reduce the amount of radiation harmful to the skin. This study aimed to formulate a lotion preparation from red betel leaf extract that has activity as a sunscreen. Red betel leaf (Piper crocatum Ruiz & Pav) was extracted using the maceration method. Preparation formulations were made with variations of red betel leaf ethanol extract in each formula, namely with concentrations of 0.04% (F1), 0.05% (F2), 0.06% (F3), and base control (F0). The activity of sunscreen lotion extract is based on the Sun Protection Factor (SPF) value using UV-VIS spectrophotometry at wavelengths of 290–320 nm using the Mansur equation. The results of the SPF value of the lotion are F1 of 13.48, F2 of 16.71, and F3 of 18.7. The evaluation of the lotion results obtained a light green lotion with M/A emulsion type that met the requirements, including homogeneity, pH, spreadability, viscosity, centrifugation test, and freeze and thaw test. Research results show that betel leaf extract lotion is physically stable and has a high SPF value, so it has the potential to be a sunscreen.